Rapid Head Movements in Common Marmoset Monkeys - Pandey, Swarnima; Simhadri, Sravanthi; Zhou, Yi (iScience, 2020)
Gaze shifts, the directing of the eyes to an approaching predator, preferred food source, or potential mate, have universal biological significance for the survival of a species. Our knowledge of gaze behavior is based primarily on visually triggered responses, whereas head orientation triggered by auditory stimuli remains poorly characterized. Common marmoset (Callithrix jacchus) is a diurnal, small-bodied (∼350 g), New World monkey species, known for its rich behavioral repertoires during social interactions. We used a lightweight head tracking system to measure marmosets' reflexive head orientations toward a natural stimulus presented from behind. We found that marmoset could rotate its head at angular velocities above 1,000°/s and maintained target accuracy for a wide range of rotation amplitudes (up to 250°). This unusual, saccadic head orienting behavior offers opportunities for understanding the many biological factors that have shaped the evolution of sensorimotor controls of gaze orientation by the primate brain. [Display omitted] •Marmosets can make rapid, reflexive head turns in response to natural stimuli•The peak velocity of marmoset head turns can exceed that of primate eye saccades•When the environment is lit, head movements are faster than when it is dark Biological Sciences; Neuroscience; Behavioral Neuroscience; Sensory Neuroscience